Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To find the expression equivalent to \(7 x^2 \sqrt{2 x^4} \cdot 6 \sqrt{2 x^{12}}\), let's go through the steps of simplification step by step.
First, we need to simplify the square roots within the expression.
1. Simplify \(\sqrt{2 x^4}\):
[tex]\[ \sqrt{2 x^4} = \sqrt{2} \cdot \sqrt{x^4} = \sqrt{2} \cdot x^2 \][/tex]
2. Simplify \(\sqrt{2 x^{12}}\):
[tex]\[ \sqrt{2 x^{12}} = \sqrt{2} \cdot \sqrt{x^{12}} = \sqrt{2} \cdot x^6 \][/tex]
Now, substitute these simplified forms back into the original expression:
[tex]\[ 7 x^2 \sqrt{2 x^4} \cdot 6 \sqrt{2 x^{12}} = 7 x^2 (\sqrt{2} \cdot x^2) \cdot 6 (\sqrt{2} \cdot x^6) \][/tex]
Next, combine like terms and constants:
[tex]\[ 7 x^2 \cdot \sqrt{2} \cdot x^2 \cdot 6 \cdot \sqrt{2} \cdot x^6 \][/tex]
First, multiply the constants:
[tex]\[ 7 \cdot 6 = 42 \][/tex]
Combine the square roots:
[tex]\[ \sqrt{2} \cdot \sqrt{2} = \sqrt{2^2} = \sqrt{4} = 2 \][/tex]
So the expression becomes:
[tex]\[ 42 x^2 \cdot x^2 \cdot x^6 \cdot 2 \][/tex]
Combine the terms with \(x\):
[tex]\[ x^2 \cdot x^2 \cdot x^6 = x^{2+2+6} = x^{10} \][/tex]
Now, multiply all components together:
[tex]\[ 42 \cdot 2 \cdot x^{10} = 84 x^{10} \][/tex]
Therefore, the equivalent expression is:
\[
\boxed{84 x^{10}}
\
First, we need to simplify the square roots within the expression.
1. Simplify \(\sqrt{2 x^4}\):
[tex]\[ \sqrt{2 x^4} = \sqrt{2} \cdot \sqrt{x^4} = \sqrt{2} \cdot x^2 \][/tex]
2. Simplify \(\sqrt{2 x^{12}}\):
[tex]\[ \sqrt{2 x^{12}} = \sqrt{2} \cdot \sqrt{x^{12}} = \sqrt{2} \cdot x^6 \][/tex]
Now, substitute these simplified forms back into the original expression:
[tex]\[ 7 x^2 \sqrt{2 x^4} \cdot 6 \sqrt{2 x^{12}} = 7 x^2 (\sqrt{2} \cdot x^2) \cdot 6 (\sqrt{2} \cdot x^6) \][/tex]
Next, combine like terms and constants:
[tex]\[ 7 x^2 \cdot \sqrt{2} \cdot x^2 \cdot 6 \cdot \sqrt{2} \cdot x^6 \][/tex]
First, multiply the constants:
[tex]\[ 7 \cdot 6 = 42 \][/tex]
Combine the square roots:
[tex]\[ \sqrt{2} \cdot \sqrt{2} = \sqrt{2^2} = \sqrt{4} = 2 \][/tex]
So the expression becomes:
[tex]\[ 42 x^2 \cdot x^2 \cdot x^6 \cdot 2 \][/tex]
Combine the terms with \(x\):
[tex]\[ x^2 \cdot x^2 \cdot x^6 = x^{2+2+6} = x^{10} \][/tex]
Now, multiply all components together:
[tex]\[ 42 \cdot 2 \cdot x^{10} = 84 x^{10} \][/tex]
Therefore, the equivalent expression is:
\[
\boxed{84 x^{10}}
\
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.